A Study on Cyber Threat Intelligence Based on Current Trends and Future Perspectives - Burak Cinar (Advances and Challenges in Science and Technology Vol. 5, 2023)
This goal of this chapter is to undertake a review of the prior CTI research that has already been conducted. The Internet of things (IoT) describes devices with sensors, processing ability, software and other technologies that connect and exchange data with other devices and systems over the Internet or other communications networks. The Internet of things encompasses electronics, communication and computer science engineering. Internet of things has been considered a misnomer because devices do not need to be connected to the public internet, they only need to be connected to a network, and be individually addressable. In current quickly changing threat landscape, which is emerging at a rapid rate, several firms are constantly put in risk by sophisticated and malicious cyber assaults. Cybercriminals nowadays are more knowledgeable, well-organized, and wealthy than in the past. CTI, or Cyber Threat Intelligence, has become a hot issue and is now being looked at by many businesses as a viable countermeasure to the rise in cyberattacks. The most fundamental question about what CTI is investigated through the process of doing a literature study. This is done by contrasting several definitions in order to identify areas of agreement and disagreement. It has been discovered that neither the organization nor the suppliers have a comprehensive grasp of the information that is deemed to be CTI; hence, further study is required in order to define CTI. This article also listed existing CTI products and services, including as threat intelligence data feeds, threat intelligence standards, and tools that are being utilized in CTI. This study outlines four research issues in cyber threat intelligence and assesses contemporary work carried out in each of those areas. Following a review of the CTI means, norms, and technology, several challenges were identified. The requirement for skilled threat data analysts who can fully exploit CTI and turn the data into useful information increases as soon as a business is bombarded with a significant volume of threat data. Even though the issue of poor data quality is not new, further research in this area is necessary given the growing use of CTI.